Support for secondary battery, solid electrolyte sheet, and secondary battery

KR1020260138481APending Publication Date: 2026-09-18NIPPON KODOSHI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020267017454
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-01-15
Filing Date
2024-01-23
Publication Date
2026-09-18

Smart Images

  • Figure PCT00001
    Figure PCT00001
  • Figure PCT00002
    Figure PCT00002
Patent Text Reader

Abstract

A support for a secondary battery is formed as a support for maintaining a solid electrolyte of a secondary battery, comprising at least one type selected from paper and nonwoven fabric, and formed from fibrillated fibers and non-fibrillated fibers, with a permeability of perfluoropolyether in the thickness direction of 2 to 30%.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a support for a secondary battery that holds a solid electrolyte, a solid electrolyte sheet, and a secondary battery having the support. Background Technology

[0002] As a secondary battery with high energy density, a lithium-ion secondary battery using a liquid electrolyte (hereinafter referred to as electrolyte) is used. A lithium-ion secondary battery using an electrolyte has a configuration in which a separator is interposed between the positive electrode and the negative electrode, and the electrolyte is retained in the separator.

[0003] In lithium-ion rechargeable batteries, organic electrolytes are primarily used as the electrolyte. Since organic electrolytes are liquids, there are concerns regarding issues such as liquid leakage and flammability. For this reason, to enhance the safety of lithium-ion rechargeable batteries, rechargeable batteries using solid electrolytes instead of liquid electrolytes (hereinafter referred to as all-solid-state batteries) are being developed. Since the electrolyte in all-solid-state batteries is naturally solid, there is no liquid leakage. Furthermore, compared to liquid electrolytes, they are flame-retardant and have high heat resistance, so they are attracting attention as rechargeable batteries with excellent safety. Because all-solid-state batteries possess high safety, small all-solid-state batteries are being mass-produced, such as for wearable devices that come into direct contact with the skin.

[0004] Furthermore, unlike lithium-ion rechargeable batteries that use liquid electrolytes, all-solid-state batteries exhibit minimal performance degradation at high temperatures, eliminating the need for cooling devices. This makes them advantageous for improving energy density per unit volume of the battery pack. As all-solid-state batteries offer advantages as rechargeable batteries with high volumetric energy density, further scaling up is anticipated, particularly for applications such as electric vehicles.

[0005] Unlike secondary batteries that use an electrolyte between the positive and negative electrodes, all-solid-state batteries have a solid electrolyte layer interposed instead of a separator that retains the electrolyte. For example, in the case of a lithium-ion all-solid-state battery, during charging, lithium ions reach the negative electrode from the positive electrode through the solid electrolyte layer.

[0006] Meanwhile, during discharge, lithium ions reach the anode from the cathode through the solid electrolyte layer. As such, regarding the ion species (hereinafter referred to as carrier ions) that conduct between the anode and cathode, in the case of all-solid-state batteries, various ion species such as sodium ions, in addition to lithium ions, are being considered from the perspective of avoiding the problem of stable resource supply. Since these carrier ions move between the anode and cathode through the solid electrolyte layer, it is necessary to form a carrier ion pass line in the thickness direction of the solid electrolyte layer.

[0007] In other words, the solid electrolyte layer interposed between the positive and negative electrodes of an all-solid-state battery is required to have the function of ion conduction of carrier ions between the positive and negative electrodes, as well as the function of preventing short circuits between the positive and negative active materials. Additionally, in order to achieve excellent volumetric energy density and low internal resistance, the thickness of the solid electrolyte layer is required to be thin.

[0008] As a method for forming a solid electrolyte layer, methods such as mixing a solid electrolyte and a binder and rolling them under heat to form a sheet, or applying a solid electrolyte slurry onto an electrode and drying it are employed.

[0009] However, when forming a solid electrolyte layer for all-solid-state batteries used in large batteries, such as those for electric vehicles, a solid electrolyte layer obtained by, for example, rolling under heat to form a sheet shape may develop cracks or fissures during handling. In addition, if a method is used in which a slurry containing a solid electrolyte is applied to an electrode and dried, deformation occurs in the solid electrolyte layer during drying, and cracks develop. For this reason, it is difficult to form a stable, thin, and uniform solid electrolyte layer. If a stable, thin, and uniform solid electrolyte layer cannot be formed, ion conductivity deteriorates, and furthermore, a short circuit occurs.

[0010] On the other hand, while the thickness of the solid electrolyte layer can be increased to prevent short circuits, a thicker layer leads to a decrease in volumetric energy density or an increase in gap distance, resulting in higher internal resistance.

[0011] To solve the above problems, it has been proposed to use a solid electrolyte sheet in an all-solid-state battery in which the solid electrolyte and the support are integrated by including a solid electrolyte in a thin-film sheet (hereinafter referred to as a support). Furthermore, various configurations regarding a support for an all-solid-state battery and a nonwoven fabric substrate for a lithium secondary battery separator have been proposed.

[0012] For example, a technology relating to a solid electrolyte sheet having a plurality of through holes formed by etching a film serving as a support is disclosed (see, for example, Patent Document 1). In this technology, an all-solid-state battery with excellent energy density and output characteristics is constructed by filling the through holes formed by the etching process with a solid electrolyte.

[0013] In addition, technology regarding a solid electrolyte sheet using a support having a porosity of 60% or more and 95% or less and a thickness of 5 μm or more and less than 20 μm is disclosed (see, for example, Patent Document 2). It is disclosed that this solid electrolyte sheet has a thin thickness and is self-standing.

[0014] In addition, a technology regarding a nonwoven fabric substrate for a lithium secondary battery separator is disclosed, comprising unoriented polyester fibers and wet-heat adhesive fibers as binder fibers (see, for example, Patent Document 3). In this technology, it is disclosed that the unoriented polyester fibers are softened or melted by hot-pressure treatment such as a calender and adhere firmly to other fibers, and the wet-heat adhesive fibers flow or easily deform in a wet state to exhibit an adhesive function. By including these binders in the nonwoven fabric substrate, a nonwoven fabric substrate for a lithium secondary battery separator with high tensile strength and high productivity is constructed. Prior art literature

[0015] Japanese Published Patent No. 2017-103146 ​​Japanese Published Patent No. 2020-77488 Japanese Published Patent No. 2020-161243 The problem to be solved

[0016] However, in the technology described in Patent Document 1, when manufacturing a solid electrolyte sheet, the solid electrolyte is filled into the through holes, so the solid electrolyte is filled only inside the formed through holes. Because of this, an insulating film portion remains outside the through holes, and an interface is formed between the positive and negative electrodes and the film portion that does not allow carrier ions to pass through. As a result, the interfacial resistance between the solid electrolyte sheet and the positive and negative electrodes tends to increase, and the resistance of the all-solid-state battery using this support increases.

[0017] In addition, in the technology described in Patent Document 2, the support is a support having sufficient pores, but if the support constituent material includes fine fibers, it becomes a support with a dense structure. As a result, it becomes difficult to infiltrate the solid electrolyte slurry into the interior of the support or to permeate it in the thickness direction. Because of this, the formation of carrier ion pass lines in the thickness direction of the solid electrolyte sheet becomes insufficient, and the solid electrolyte sheet becomes one with high internal resistance.

[0018] In addition, in the technology described in Patent Document 2, when the number of fibers constituting the support material is small, the permeability of the solid electrolyte slurry in the thickness direction of the support becomes excessively high, so there is concern regarding the retention of the solid electrolyte slurry. As a result, the solid electrolyte slurry cannot remain in the support, and the retention effect of the solid electrolyte by the support is not sufficiently obtained, and the resistance increases.

[0019] Furthermore, in the technology described in Patent Document 3, the wet-heat adhesive fibers included in the nonwoven fabric substrate undergo flow or deformation in the expression of the adhesive function as described above, so they cannot maintain their fiber state and may end up filling the voids inside the nonwoven fabric substrate. In addition, if a large amount of binder fibers that cannot maintain their fiber shape are included, the density increases. As a result, the penetration of the solid electrolyte slurry into the nonwoven fabric substrate and the permeability in the thickness direction of the nonwoven fabric substrate become insufficient. Because of this, the amount of carrier ion pass lines formed inside the solid electrolyte sheet decreases, and the resistance of the all-solid-state battery increases.

[0020] To solve the aforementioned problem, the present invention provides a support for a secondary battery capable of reducing the internal resistance of a solid electrolyte layer, a solid electrolyte sheet using the support, and a secondary battery using the support. means of solving the problem

[0021] The support for a secondary battery according to the present invention is a support for maintaining a solid electrolyte of a secondary battery, and is composed of at least one type selected from paper and nonwoven fabric, is formed of fibrillated fibers and non-fibrillated fibers, and has a permeability of perfluoropolyether in the thickness direction of 2 to 30%.

[0022] In addition, the solid electrolyte sheet of the present invention is made of at least one type selected from paper and nonwoven fabric, and a solid electrolyte is maintained on a thin film support composed of fibrillated fibers and non-fibrillated fibers, and the transmittance to perfluoropolyether in the thickness direction of the support is 2 to 30%.

[0023] In addition, the secondary battery of the present invention comprises a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. In this secondary battery, the solid electrolyte layer is composed of a solid electrolyte sheet in which a solid electrolyte is retained on a support. The solid electrolyte sheet is made of at least one type selected from paper and nonwoven fabric, and comprises a support composed of fibrillated fibers and non-fibrillated fibers, having a transmittance to perfluoropolyether in the thickness direction of 2 to 30%, and a solid electrolyte retained on the support. Effects of the invention

[0024] According to the present invention, a support for a secondary battery capable of reducing the internal resistance of a solid electrolyte layer, a solid electrolyte sheet using the support, and a secondary battery using the support for the secondary battery can be provided. Specific details for implementing the invention

[0025] The following describes examples of embodiments for carrying out the present invention, but the present invention is not limited to the following examples.

[0026] And, the explanation is carried out in the following order.

[0027] 1. Embodiment of a support for a secondary battery (First embodiment)

[0028] 2. Embodiment of a secondary battery (Second embodiment)

[0029] <1. Embodiment of a support for a secondary battery (First embodiment)>

[0030] Hereinafter, a support for a secondary battery is described in specific embodiments.

[0031] A support for a secondary battery of the present type (hereinafter also simply referred to as a support) is used to form a solid electrolyte layer interposed between a positive electrode and a negative electrode in a secondary battery. The support is configured to support the solid electrolyte of the secondary battery and comprises at least one material selected from paper and nonwoven fabric, and has a permeability of perfluoropolyether in the thickness direction of 2 to 30%. Furthermore, the numerical range indicated by "~" in the present disclosure includes numerical values ​​indicated as upper and lower limits.

[0032] The solid electrolyte layer interposed between the anode and the cathode is required to conduct carrier ions between the anode and the cathode during charging and discharging. To achieve this, it is necessary to form carrier ion pass lines between the anode and the solid electrolyte layer, within the solid electrolyte layer, and between the solid electrolyte layer and the cathode. In other words, if the interfacial resistance between the anode and the solid electrolyte layer, and between the solid electrolyte layer and the cathode, as well as the resistance within the solid electrolyte layer, can be reduced, the resistance of the all-solid-state battery can be lowered.

[0033] The inventors have discovered that the permeability of the liquid in the thickness direction of the support is a factor that hinders further reduction of the internal resistance of the solid electrolyte sheet. Accordingly, in the support according to the present form, unlike the permeability of conventional gases, the diffusion of the solid electrolyte slurry into the support and the retention of the liquid by the support are evaluated by using a liquid, just as in actual coating.

[0034] If the permeability of the liquid in the thickness direction of the support is excessively low, the number of carrier ion pass lines formed inside the solid electrolyte sheet decreases. On the other hand, if the permeability of the liquid in the thickness direction of the support is excessively high, the retention of the solid electrolyte slurry by the support is low, resulting in less solid electrolyte slurry remaining on the support and consequently fewer carrier ion pass lines formed inside the solid electrolyte sheet. Consequently, in either of the aforementioned cases, the resistance of the solid electrolyte sheet obtained increases.

[0035] Accordingly, by optimizing the liquid permeability in the thickness direction of the support, the number of carrier ion pass lines formed inside the solid electrolyte sheet can be increased. As a result, the resistance of the solid electrolyte layer can be reduced.

[0036] In this embodiment, the permeability of perfluoropolyether in the thickness direction is adopted as an indicator for measuring the permeability of a liquid in the thickness direction of a support. Since perfluoropolyether is a chemically inert and low-surface-tension substance that is liquid at room temperature, it is a liquid that can evaluate permeability in the thickness direction based on the internal structure of the support.

[0037] For example, if the same evaluation is performed in water, if the hydrophilicity of the support is high, the constituent fibers of the support swell under the influence of water, causing the internal structure of the support to change. Furthermore, if the hydrophilicity of the support is low, the wettability to the support is low, which reduces penetration into the support, making it impossible to accurately determine the penetration and permeability based on the structure of the support. Additionally, since water has high surface tension, it hinders the penetration or permeation of water into the support, making it impossible to accurately evaluate the influence of the internal structure of the support. Moreover, for example, if the same evaluation is performed in a general organic solvent, the organic solvent has a low vapor pressure, so the organic solvent evaporates during the test, making it impossible to determine the accurate amount of permeation.

[0038] That is, since perfluoropolyethers have less interaction with the support compared to other liquids, the influence of the measurement solution on the fibers constituting the support is minor, so the inherent characteristics of the support can be accurately evaluated for supports of different types of fibers. In addition, in this invention, Propene, 1,1,2,3,3-Hexafluoro, oxidized, Polymerized (surface tension 16 mN / m) is used as the perfluoropolyether.

[0039] The amount of perfluoropolyether permeated in the thickness direction is the mass of perfluoropolyether that is dropped in a predetermined amount onto the surface of a support, penetrates and diffuses into the interior of the support, and permeates to the back surface of the support.

[0040] The permeability of perfluoropolyether in the thickness direction was calculated by dividing the amount of perfluoropolyether permeating in the thickness direction by the mass of the perfluoropolyether added and taking the result as a percentage. In other words, by determining the permeability of perfluoropolyether, the permeability of the solid electrolyte slurry in the thickness direction of the support can be determined.

[0041] If the permeability of perfluoropolyether in the thickness direction is low, it indicates that the permeability of the solid electrolyte slurry in the thickness direction of the support is low. On the other hand, if the permeability of perfluoropolyether in the thickness direction is high, the permeability of the solid electrolyte slurry into the support is excessively high, so the retention of the solid electrolyte slurry into the support is reduced.

[0042] The support has a permeability of perfluoropolyether in the thickness direction controlled to a range of 2 to 30%.

[0043] A support having a perfluoropolyether permeability in the thickness direction within the above range has excellent permeability and retention of the solid electrolyte slurry in the thickness direction of the support, so the solid electrolyte slurry can be impregnated uniformly in the required amount within the support. As a result, a required amount of carrier ion pass lines can be formed within the solid electrolyte sheet obtained. Due to the above effects, the internal resistance of the solid electrolyte layer can be reduced. That is, by using this support, the resistance of the all-solid-state battery can be lowered.

[0044] In addition, in terms of permeability and retention of the support to the solid electrolyte slurry, it is more desirable that the permeability of the perfluoropolyether in the thickness direction of the support be in the range of 4 to 25%.

[0045] If the permeability of perfluoropolyether in the thickness direction of the support is less than the above range, the amount of solid electrolyte slurry permeating in the thickness direction of the support is insufficient, so the number of carrier ion pass lines formed in the thickness direction inside the solid electrolyte sheet decreases.

[0046] Meanwhile, if the permeability of perfluoropolyether in the thickness direction of the support exceeds the above range, a large amount escapes to the back side, and the amount of solid electrolyte slurry that the support can retain is small. As a result, the number of carrier ion pass lines formed in the thickness direction inside the solid electrolyte sheet decreases, and the internal resistance of the solid electrolyte sheet increases.

[0047] If the permeability of the perfluoropolyether is within the above range, other components of the support, such as thickness, basis weight, density, porosity, and tensile strength, are not particularly limited. If the permeability of the perfluoropolyether is within the above range, it is possible to evaluate that sufficient carrier ion pass lines are formed within the solid electrolyte sheet without being limited to the composition of the support, thereby reducing the internal resistance of the solid electrolyte sheet and lowering the resistance of the all-solid-state battery. In terms of the permeability, retention, and tensile strength of the support with respect to the solid electrolyte slurry, the basis weight of the support is 1.0 to 15.0 g / m² 2 It is more desirable to limit it to the range of.

[0048] The support is composed of at least one material selected from paper and nonwoven fabric. Preferably, the support is composed of only at least one of paper and nonwoven fabric. This is due to the following reasons.

[0049] Paper refers to a material manufactured by fixing plant fibers or other fibers. Furthermore, nonwoven fabric refers to a sheet-type material made by bonding constituent fibers together using adhesives or the adhesive force of the fibers themselves, without using a loom, by treating various fiber webs, such as natural, regenerated, or synthetic fibers, mechanically, chemically, thermally, or a combination thereof.

[0050] That is, since paper and nonwoven fabrics have a composition in which fibers are randomly arranged, they contain countless pores of various sizes or through holes of various sizes within them. Because of this, the applied solid electrolyte slurry can spread not only in the thickness direction but also in the plane direction. That is, the applied solid electrolyte may remain on the surface of the support, remain inside the support, or pass through the through holes from the surface side and reach the back side.

[0051] For this reason, a solid electrolyte sheet fabricated using at least one of paper and nonwoven fabric as a support can form a good carrier ion pass line, in which the solid electrolyte is filled not only on the surface of the support but also inside the support. As a result, along with a reduction in the internal resistance of the solid electrolyte sheet, the interfacial resistance between the solid electrolyte sheet and the anode or cathode can be lowered. Consequently, this can lead to a reduction in the resistance of the all-solid-state battery.

[0052] The materials that can be used as materials constituting the support are not particularly limited as long as they are fibers that do not repel the solid electrolyte slurry and do not have an adverse effect on the solid electrolyte physically or chemically. Examples include organic fibers such as cellulose fibers, polyamide fibers, polyester fibers, polypropylene fibers, and acrylic fibers, or inorganic fibers such as glass fibers and alumina fibers. In addition, one or more fibers selected from these fibers may be used. By using these fibers, a support with excellent packing properties for the solid electrolyte can be obtained.

[0053] In addition, from the perspective of maintaining the shape of the support and tensile strength, it is desirable for the support to contain fibers having adhesive properties. Examples of fibers having adhesive properties include fibers having fibrils on the fiber surface (hereinafter referred to as fibrillated fibers), synthetic resin binder fibers, etc.

[0054] For example, the adhesive strength of fibrillated cellulose fibers consists of physical bonding through the entanglement of the cellulose fibers and chemical bonding through hydrogen bonding of the hydroxyl groups of the cellulose. Additionally, the adhesive strength of fibrillated polyamide fibers and fibrillated acrylic fibers consists of physical bonding through the entanglement of the fibers. Since bonding by any of the fibers contributes to maintaining the shape of the support and developing tensile strength, it is desirable.

[0055] Synthetic resin binder fibers include those that maintain a fibrous state while forming a support, and those that cannot maintain a fibrous state and are, for example, in a film form. Binder fibers that maintain a fibrous state while forming a support are preferred in that they are less likely to impair permeability and can also improve the tensile strength of the support.

[0056] Binder fibers that maintain a fiber shape while forming a support exhibit adhesive strength by heat-bonding fiber entanglement points. For this reason, binder fibers that maintain a fiber state as a constituent material of the support can reduce breakage due to physical impact, and since adhesion occurs only at fiber contact points, it is difficult to hinder the penetration and permeation of solid electrolyte slurry into the support when forming a solid electrolyte sheet.

[0057] On the other hand, synthetic resin binder fibers that cannot maintain a fiber state while forming a support structure are subjected to heat during the support manufacturing process, causing the fibers to change into a film form. Since heat is applied near the melting point or softening point of the resin constituting the fibers, the resin melts and fuses at the entanglement points of the fibers. In other words, when a binder that is not in a fiber state is used while forming a support structure, the binder component forms a film layer in the fiber gaps of the support structure and fills the pores when the binder function is manifested. As a result, the penetration and permeation of the solid electrolyte into the support structure may be inhibited, and care must be taken with the content ratio when using it.

[0058] Materials that can be used as synthetic resin binder fibers that maintain a fiber shape with adhesive properties are not particularly limited, provided they are fibers that do not repel solid electrolyte slurries and do not have an adverse effect on the solid electrolyte physically or chemically. Examples include fibrillated fibers such as refined cellulose fibers, refined polyamide fibers, and refined acrylic fibers, polyamide binder fibers, polyester binder fibers, polyethylene binder fibers, and polypropylene-polyethylene core-sheath type binder fibers. Additionally, one or more fibers selected from these fibers may be used.

[0059] The support comprises both fibrillated fibers and fibers that do not have fibrils (hereinafter referred to as non-fibrillated fibers). That is, the support is composed of at least one type selected from paper and nonwoven fabric, and is composed of fibrillated fibers and non-fibrillated fibers.

[0060] Fibrillated fibers have branch-like fibrils on their surface, allowing for a large number of fibers to support the solid electrolyte and enabling uniform support of the solid electrolyte. On the other hand, non-fibrillated fibers do not have branch-like fibrils on their surface; therefore, when the solid electrolyte is infiltrated into the support, the fibers do not hinder the infiltration of the solid electrolyte, and the solid electrolyte infiltrates uniformly along the thickness direction of the support.

[0061] That is, a support composed of fibrillated fibers and non-fibrillated fibers has permeability of the solid electrolyte slurry in the thickness direction of the support, and the solid electrolyte has uniform support.

[0062] As a result, a uniform solid electrolyte sheet is obtained using a support of the above configuration. That is, a solid electrolyte sheet with low resistance is obtained.

[0063] In addition, the support is not particularly constrained by the content of fibrillated fibers and non-fibrillated fibers relative to the total fibers constituting the support, or the ratio of fibrillated fibers to non-fibrillated fibers. Preferably, the support contains 1 to 99 mass% of fibrillated fibers relative to the total fibers constituting the support. More preferably, the support contains 50 to 85 mass% of fibrillated fibers relative to the total fibers constituting the support.

[0064] As a method to achieve a perfluoropolyether permeability in the thickness direction of a support in the range of 2 to 30%, for example, in the case of fibrillated fibers, the fiber length can be controlled to 0.1 to 2 mm. To obtain fibrillated fibers with a fiber length of 0.1 to 2 mm, for example, there is a method of refining the fibers until the CSF ("Canadian Standard" freeness) value becomes 0 to 400 ml. In addition, in the case of non-fibrillated fibers, the average fiber diameter of the non-fibrillated fibers can be controlled to 1 to 15 μm and the fiber length to 1 to 6 mm. Furthermore, as long as the perfluoropolyether permeability in the thickness direction can be achieved in the range of 2 to 30%, it is not limited to this.

[0065] There are no particular limitations on the method of manufacturing the support, and it can be manufactured by a dry method or a wet method; however, preferably, a papermaking method in which fibers dispersed in water are deposited onto a wire, dehydrated, dried, and then lifted is preferred from the perspective of the homogeneity of the paper quality of the support. The papermaking form of the support is not particularly limited as long as it can satisfy the permeability of perfluoropolyether in the thickness direction, and papermaking forms such as long-net papermaking, short-net papermaking, and circular-net papermaking may be adopted, and multiple layers formed by these papermaking methods may also be combined. Furthermore, during papermaking, additives such as dispersants, defoaming agents, and strength enhancers may be added, and after the paper layer is formed, post-processing such as strength-enhancing processing, hydrophilic processing, calendering, thermal calendering, and embossing may be performed.

[0066] <2. Embodiment of a secondary battery (Second embodiment)>

[0067] Next, an embodiment of a secondary battery using the aforementioned support will be described. The secondary battery is, for example, an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer. In this case, the solid electrolyte layer is arranged to be interposed between the positive electrode and the negative electrode. The solid electrolyte layer is composed of a solid electrolyte sheet in which a solid electrolyte is retained on a support. The solid electrolyte sheet comprises a support for a secondary battery and a solid electrolyte, and has a configuration in which the solid electrolyte is retained on the support and the solid electrolyte and the support are integrated.

[0068] The types of positive and negative electrodes used in all-solid-state batteries are not particularly limited. For example, in an all-solid-state battery, it may be composed of known positive and negative electrodes, but it is not limited to these.

[0069] In addition, the type of all-solid-state battery is not particularly limited, and depending on the selection of the material constituting the all-solid-state battery, it can be formed into, for example, a lithium-ion secondary battery, a sodium-ion secondary battery, etc.

[0070] The above-mentioned all-solid-state battery can be used as a storage battery for, for example, mobile communication devices, electronic devices for mobile phones, electric bicycles, electric motorcycles, electric vehicles, small household power storage devices, etc.

[0071] [Polygonal, Cathode]

[0072] In a secondary battery, the positive active material used in the positive layer and the negative active material used in the negative layer are not particularly limited and only need to function as the positive and negative electrodes of an all-solid-state battery according to various carrier ions.

[0073] The positive electrode is formed with a layer containing a positive electrode active material and a positive electrode current collector. For example, if the all-solid-state battery is a lithium-ion secondary battery, the positive electrode needs to be composed of a material capable of absorbing and releasing lithium ions.

[0074] As the positive current collector, for example, aluminum can be used.

[0075] As cathode active materials, examples of sulfide-based materials include titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), and nickel sulfide (Ni3S2). In addition, oxide-based materials include bismuth oxide (Bi2O3), bismuth lead oxide (Bi2Pb2O5), copper oxide (CuO), and vanadium oxide (V6O). 13 Examples include lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganate (LiMnO2), Li(NiCoMn)O2, Li(NiCoAl)O2, and Li(NiCo)O2. It is also possible to use a mixture of these.

[0076] In addition, the negative electrode is formed with a negative electrode current collector and a layer containing a negative electrode active material. For example, if the all-solid-state battery is a lithium-ion secondary battery, metallic lithium, metallic indium, or a material capable of absorbing and releasing lithium ions can be used as the negative electrode active material.

[0077] For example, copper can be used as the cathode current collector.

[0078] Examples of cathode active materials include carbon materials, specifically artificial graphite, graphite carbon fibers, resin-fired carbon, pyrolytic gas-phase grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-fired carbon, polyacene, pitch-based carbon fibers, gas-phase grown carbon fibers, natural graphite, non-graphitizable carbon, etc. Alternatively, a mixture of these may be used. In addition, examples include metals themselves such as metallic lithium, metallic indium, metallic aluminum, or metallic silicon, or alloys combining these metals with other elements or compounds.

[0079] The positive and negative electrodes constituting the all-solid-state battery are selected from two types of materials capable of constituting electrodes, and the charge / discharge potentials of the two types of compounds are compared, and the one exhibiting a positive potential is used as the positive electrode and the one exhibiting a negative potential is used as the negative electrode to constitut any battery.

[0080] [Solid Electrolyte Layer]

[0081] In an all-solid-state battery, the solid electrolyte layer is composed of a solid electrolyte sheet in which a solid electrolyte is retained on a support. The type of solid electrolyte constituting the solid electrolyte sheet is not particularly limited, and, for example, known materials that can be used as solid electrolytes for all-solid-state batteries may be used.

[0082] Furthermore, the solid electrolyte is not particularly limited and only needs to be capable of carrier ion conduction between the anode and the cathode. Examples include oxide-based solid electrolytes and sulfide-based solid electrolytes. Additionally, other components, such as binders, may be added as needed.

[0083] For example, as lithium-ion conductive sulfide-based solid electrolytes, there are sulfide-based amorphous solid electrolytes and sulfide-based crystalline solid electrolytes. Specific examples of sulfide-based amorphous solid electrolytes include Li2S-SiS2, Li2S-GeS2, Li2, S-P2S5, Li2S-B2S3, Li2S-SiS2-Li3PO4, Li2S-S, iS2-Li2SO4, Li2S-P2S5-LiI, Li2S-P2S5-P2O5-, LiI, Li2S-B2S3-LiI, Li2S-P2S5-Li2O-LiI, Li2, S-SiS2-B2S3-LiI, etc.

[0084] In addition, sulfide-based amorphous solid electrolytes may contain other elements.

[0085] In addition, as a specific example of a sulfide-based crystalline solid electrolyte, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 Examples include Li6PS5Cl, but sulfide-based crystalline solid electrolytes are not limited to the composition of these elements.

[0086] The solid electrolyte may be any solid electrolyte other than a sulfide-based solid electrolyte or an oxide-based solid electrolyte, and as other examples, semi-solid polymer electrolytes containing carrier ions, such as polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, or polyacrylonitrile, are also exemplified. The solid electrolyte may be a so-called gel-type electrolyte in which an electrolyte solution is retained in a polymer solid electrolyte, such as a polyethylene oxide-based polymer, a polymer containing at least one selected from polyorganosiloxane chains and polyoxyalkylene chains.

[0087] [Method for manufacturing solid electrolyte sheets]

[0088] The method for manufacturing the solid electrolyte sheet is not particularly limited, and conventional methods in the field of technology may be applied.

[0089] For example, there is a method of preparing a slurry in which a solid electrolyte is dispersed in a solvent, applying the prepared slurry to a support, and drying it. The solvent used to prepare the solid electrolyte slurry is not particularly limited, as long as it does not adversely affect the performance of the solid electrolyte. For example, non-aqueous solvents are used.

[0090] As a coating method for applying a slurry containing a solid electrolyte to both sides or one side of a support, examples include slide die coating, comma die coating, comma reverse coating, gravure coating, gravure reverse coating, etc., although not particularly limited.

[0091] Drying of a slurry containing a solid electrolyte after application can be performed, for example, by a drying device using hot air, a heater, high frequency, etc.

[0092] In addition, the solid electrolyte sheet can be used as a dry sheet, but its mechanical strength or density can be increased by applying further pressure. Methods of applying pressure include, for example, sheet presses or roll presses.

[0093] [Method for manufacturing all-solid-state batteries]

[0094] A solid-state battery can be manufactured by placing a solid electrolyte layer, including a solid electrolyte sheet, between the anode layer and the cathode layer described above, and bonding them. The bonding method is not particularly limited, but examples include a method of stacking each sheet and pressing and compressing them, or a method of passing them between two rolls and pressing them (roll to roll).

[0095] In addition, for the purpose of improving adhesion between the solid electrolyte layer and the anode or cathode layer, an ion-conductive active material or an adhesive material that does not impede ion conductivity may be placed at the bonding interface.

[0096] [Example]

[0097] Hereinafter, specific embodiments of the support body according to the embodiments of the present invention will be described.

[0098] First, the supports of Examples 1 to 4 and Comparative Examples 1 to 6 were prepared by the following method. Then, except for Comparative Example 3, the supports were prepared as paper formed using a papermaking method or as wet nonwoven fabrics.

[0099] [Example 1]

[0100] Using a raw material mixed with 85 mass% of cellulose fibers having a CSF value of 0 ml and an average fiber length of 0.2 mm, and 15 mass% of non-fibrillated cellulose fibers having an average fiber diameter of 5 μm and an average fiber length of 3 mm, the material was papered into a long mesh to obtain a thickness of 25 μm and a basis weight of 14.0 g / m² 2 , density 0.56 g / cm³ 3 A support structure was obtained.

[0101] [Example 2]

[0102] Using a raw material mixed with 55 mass% of polyamide fibers having a CSF value of 400 ml and an average fiber length of 1.8 mm, and 45 mass% of polyester binder fibers having an average fiber diameter of 2 μm and an average fiber length of 2 mm, single-mesh paper was produced to obtain a thickness of 8 μm and a basis weight of 1.4 g / m² 2 , density 0.18 g / cm³ 3 A support structure was obtained.

[0103] [Example 3]

[0104] Using a raw material mixed with 65 mass% of cellulose fibers having a CSF value of 150 ml and an average fiber length of 1.2 mm, and 35 mass% of polyester fibers having an average fiber diameter of 8 μm and an average fiber length of 5 mm, rotary papermaking was performed to produce a thickness of 20 μm and a basis weight of 8.4 g / m² 2 , density 0.42 g / cm³ 3 A support structure was obtained.

[0105] [Example 4]

[0106] Using a raw material mixed with 70 mass% of cellulose fibers having a CSF value of 30 ml and an average fiber length of 0.8 mm, and 30 mass% of polyamide fibers having an average fiber diameter of 15 μm and an average fiber length of 6 mm, single-mesh paper was produced to obtain a thickness of 15 μm and a basis weight of 5.3 g / m² 2 , density 0.35 g / cm³ 3 A support structure was obtained.

[0107] [Example 5]

[0108] Long mesh papermaking was performed using a raw material comprising 99 mass% of cellulose fibers with a CSF value of 5 ml and an average fiber length of 0.5 mm, and 1 mass% of polyamide binder fibers with an average fiber diameter of 8 μm and an average fiber length of 3 mm. The obtained nonwoven fabric was calendered to obtain a thickness of 25 μm and a basis weight of 15.0 g / m². 2 , density 0.60 g / cm³ 3 A support structure was obtained.

[0109] [Example 6]

[0110] Using a raw material mixed with 1 mass% of acrylic fibers with a CSF value of 50 ml and an average fiber length of 1.0 mm, 19 mass% of non-fibrillated acrylic fibers with an average fiber diameter of 10 μm and an average fiber length of 3 mm, and 80 mass% of polyester binder fibers with an average fiber diameter of 5 μm and an average fiber length of 3 mm, a single-mesh paper is produced with a thickness of 10 μm and a basis weight of 1.6 g / m² 2 , density 0.16 g / cm³ 3 A support structure was obtained.

[0111] [Comparative Example 1]

[0112] A raw material comprising 15 mass% of polyester fibers having an average fiber diameter of 16 μm and an average fiber length of 5 mm, and 85 mass% of polyester binder fibers having an average fiber diameter of 4 μm and an average fiber length of 3 mm was used, and a circular paper was formed by referring to the method for manufacturing a support described in Example 1 of Patent Document 2, to obtain a thickness of 19 μm and a basis weight of 3.8 g / m² 2 , density 0.20 g / cm³ 3A support structure was obtained.

[0113] [Comparative Example 2]

[0114] A raw material comprising 40 mass% of polyester fibers with an average fiber diameter of 2.3 μm and an average fiber length of 3 mm, 50 mass% of polyester binder fibers with an average fiber diameter of 4.2 μm and an average fiber length of 3 mm, and 10 mass% of ethylene-vinyl alcohol fibers with an average fiber diameter of 7.2 μm and an average fiber length of 5 mm was used, and by referring to the method for manufacturing a support described in Example 1 of Patent Document 3, the material was processed by single-mesh papermaking and thermal calendering to obtain a thickness of 12 μm and a basis weight of 7.0 g / m² 2 , density 0.58 g / cm³ 3 A support structure was obtained.

[0115] [Comparative Example 3]

[0116] A support was prepared by the same method as described in Example 2 of Patent Document 1 to obtain the support of Comparative Example 3. In Comparative Example 3, a polyimide film was etched to form holes of 200 μm × 200 μm, and a thickness of 30 μm and a basis weight of 8.8 g / m² were obtained. 2 , density 0.29 g / cm³ 3 A support structure was obtained.

[0117] [Comparative Example 4]

[0118] Using a raw material mixed with 90 mass% of cellulose fibers having a CSF value of 0 ml and an average fiber length of 0.2 mm, and 10 mass% of non-fibrillated cellulose fibers having an average fiber diameter of 3 μm and an average fiber length of 3 mm, long mesh paper is produced to obtain a thickness of 25 μm and a basis weight of 15.5 g / m² 2 , density 0.62 g / cm³ 3 A support structure was obtained.

[0119] [Comparative Example 5]

[0120] Using a raw material comprising a mixture of 45 mass% of polyamide fibers with a CSF value of 430 ml and an average fiber length of 2.3 mm, and 55 mass% of polyester binder fibers with an average fiber diameter of 2 μm and an average fiber length of 2 mm, single-mesh paper was produced to obtain a thickness of 15 μm and a basis weight of 3.0 g / m² 2 , density 0.20 g / cm³ 3 A support structure was obtained.

[0121] [Comparative Example 6]

[0122] Using a raw material mixed with 60 mass% of cellulose fibers having a CSF value of 10 ml and an average fiber length of 0.5 mm, and 40 mass% of polyester fibers having an average fiber diameter of 0.7 μm and an average fiber length of 0.5 mm, long mesh paper was produced with a thickness of 20 μm and a basis weight of 7.9 g / m² 2 , density 0.40 g / cm³ 3 A support structure was obtained.

[0123] [Comparative Example 7]

[0124] Using a raw material mixed with 50 mass% of polyamide fibers having a CSF value of 200 ml and an average fiber length of 1.1 mm, and 50 mass% of polyester binder fibers having an average fiber diameter of 16 μm and an average fiber length of 7 mm, single-mesh paper was produced to obtain a thickness of 20 μm and a basis weight of 3.0 g / m² 2 , density 0.15 g / cm³ 3 A support structure was obtained.

[0125] [Comparative Example 8]

[0126] A single-mesh paper was produced using a raw material mixed with 70 mass% of cellulose fibers with a CSF value of 0 ml and an average fiber length of 0.04 mm, and 30 mass% of polyester fibers with an average fiber diameter of 3 μm and an average fiber length of 3 mm, but a paper layer could not be formed, so a support could not be obtained.

[0127] [Production of All-Solid State Batteries]

[0128] Next, an all-solid-state battery was fabricated using the supports of the above examples and comparative examples. The specific fabrication method is as follows.

[0129] (Bipolar structure)

[0130] LiNiCoAlO2 ternary powder was used as the positive active material, Li2S-P2S5 amorphous powder as the sulfide-based solid electrolyte, and carbon fiber as the conductive aid, respectively, and mixed. A dehydrated xylene solution in which SBR (styrene-butadiene rubber) was dissolved was mixed with this mixed powder as a binder to prepare a positive coating solution. The positive coating solution was applied to an aluminum foil current collector serving as the positive current collector, dried, and then rolled to obtain a positive structure.

[0131] (Cathode structure)

[0132] A cathode coating solution was prepared by mixing graphite as the cathode active material, Li2S-P2S5 amorphous powder as the sulfide-based solid electrolyte, PVdF (polyvinylidene fluoride) as the binder, and NMP (N-methyl-2-pyrrolidone) as the solvent. A cathode structure was obtained by applying the cathode coating solution to a copper foil current collector, drying it, and rolling it.

[0133] (Solid electrolyte sheet)

[0134] A solid electrolyte slurry was prepared by mixing Li2S-P2S5 amorphous powder as a sulfide-based solid electrolyte, SBR as a binder, and xylene as a solvent.

[0135] A solid electrolyte slurry was applied to the support of each of the above examples and each comparative example, and dried to obtain a solid electrolyte sheet.

[0136] [Manufacturing of All-Solid State Batteries]

[0137] A single cell of an all-solid-state battery was obtained by laminating a negative electrode structure of size 88mm × 58mm, a solid electrolyte sheet of size 92mm × 62mm, and a positive electrode structure of size 87mm × 57mm, performing dry lamination, and bonding.

[0138] The obtained single cell was placed in an aluminum laminate film equipped with terminals, degassed, and heat-sealed to pack it.

[0139] [Method for measuring the characteristics of supports and all-solid-state batteries]

[0140] The characteristics of the fabricated support and the all-solid-state battery were measured under the following conditions and methods.

[0141] [CSF Value]

[0142] The CSF value was measured according to JIS P8121-2 “Pulps-Determination of Drainability-Part 2: Canadian Standard Freeness Method” (ISO 5267-2 “Pulps-Determination of Drainability-Part 2: “Canadian Standard” Freeness Method)

[0143] [Average fiber length]

[0144] [Fiber length]

[0145] The apparatus described in JIS P 8226-2 “Pulps-Determination of Fiber length by automated optical analysis-Part 2: Unpolarized light method” (ISO 16065-2 “Pulps-Determination of Fiber length by automated optical analysis-Part 2: Unpolarized light method”) was used for measurement, and the Fiber Tester PLUS (manufactured by Lorentzen & Wettre) was used to determine the fiber length.

[0146] [Fiber length of polyester fibers and polyester binder fibers]

[0147] Since polyester fibers and polyester binder fibers are optically transparent, the fibers cannot be accurately recognized as images; therefore, accurate measurement of fiber length using the aforementioned optical automatic analysis method could not be performed. For this reason, the fiber lengths of polyester fibers and polyester binder fibers were measured using the following method.

[0148] A slide with randomly dispersed fibers was prepared. The fiber lengths on the slide were measured using a direct scale.

[0149] [thickness]

[0150] The measuring force of the micrometer described in “5.1.1 Measuring Instrument and Measurement Method a. When Using an External Micrometer” as specified in “JIS C 2300-2 ‘Electrical Cellulose Paper - Part II: Test Methods’ 5.1 Thickness” is 1.5 N, and the diameter of the pressure surface is 14.3 mm f Using the modified version, the thickness of the support was measured by folding and overlapping 10 sheets as per "5.1.3 Case of measuring thickness by folding and overlapping paper".

[0151] [Biographical value]

[0152] The basis weight of the support in the dry state was measured using the method specified in “JIS C 2300-2 ‘Electric Cellulose Paper - Part 2: Test Methods’ 6 Basis Weight”.

[0153] [density]

[0154] The density of the support was calculated using the following formula.

[0155] Density (g / cm³) 3 )=W / T

[0156] W: Basis weight (g / m²) 2 ), T: Thickness (μm)

[0157] [Porosity]

[0158] The porosity of the support was calculated using the following formula. In cases where multiple materials constituting the support are mixed, the average specific gravity of the constituent fibers was determined by performing a calculation proportional to the mixing ratio, and then the result was calculated.

[0159] Porosity (%) = (1 - (D / S)) × 100

[0160] D: Support density (g / cm³) 3 ), S: Specific gravity of constituent fibers (g / cm³) 3 )

[0161] [Permeability of perfluoropolyether in the thickness direction]

[0162] A test specimen cut to 50 mm × 50 mm was fixed to the bottom of a cylinder with an inner diameter of 12 mm and an outer diameter of 15 mm. The cylinder with the attached test specimen was placed so that the test specimen and the glass plate were in contact. 0.1 ml of perfluoropolyether was dropped into the cylinder, and the mass of the dropped perfluoropolyether was measured. After dropping the perfluoropolyether, the cylinder with the attached test specimen was left for 1 minute, and then removed. The mass of the perfluoropolyether adhering to the glass plate was measured after penetrating and passing through the support from the inside of the cylinder. The transmittance of the perfluoropolyether in the thickness direction of the support was calculated using the following formula.

[0163] Transmittance (%) = w2 / w1 × 100

[0164] w1: Mass of dropwise perfluoropolyether (g)

[0165] w2: Mass of perfluoropolyether passed through (g)

[0166] [tensile strength]

[0167] In accordance with the method specified in JIS P 8113 “Paper and board—Determination of tensile properties—Part 2: Constant rate of elongation method” (ISO 1924-2 “Paper and board—Determination of tensile properties—Part 2: Constant rate of elongation method”), the maximum tensile load in the longitudinal direction (manufacturing direction) of the support was measured at a test width of 15 mm and was used as the tensile strength of the support.

[0168] [Assessment of Self-Reliance]

[0169] For each fabricated solid electrolyte sheet, self-support was evaluated.

[0170] When the manufactured solid electrolyte sheet of size 92mm × 62mm was lifted while maintaining the end of the short side, if no cracks or fissures were observed in the solid electrolyte sheet with the naked eye, it was marked ○, and if cracks or fissures were observed in the solid electrolyte sheet with the naked eye when lifted, it was marked ×.

[0171] [Internal resistance of solid electrolyte sheets]

[0172] For the all-solid-state battery, charging was performed to 4.0V at a current density of 0.1C under an environment of 25℃, and the impedance in the frequency range of 0.1Hz to 1MHz was measured using an LCR meter. The arc portion of the obtained coloc plot was fitted into a semicircle shape with the X-axis as the base, and the value at the point where the right end of the semicircle intersects the X-axis was taken as the resistance value.

[0173] [Discharge capacity of solid electrolyte sheets]

[0174] For the all-solid-state battery, charging was performed to 4.0V at a current density of 0.1C under an environment of 25℃, and then discharged to 2.5V at a current density of 0.1C, and the discharge capacity at that time was measured.

[0175] Table 1 shows the names of the fibers and the mixing ratios of each support in Examples 1 to 6 and Comparative Examples 1 to 8 described above.

[0176] [Table 1]

[0177]

[0178] Table 2 shows the characteristics of each support, the self-supporting properties of the solid electrolyte sheet, and the evaluation results of the battery characteristics of each example and each comparative example described above.

[0179] [Table 2]

[0180]

[0181] Hereinafter, the evaluation results of all-solid-state batteries using the supports of each example and each comparative example will be described in detail.

[0182] The solid electrolyte sheet using the support of each embodiment was able to form a solid electrolyte sheet having self-supporting properties.

[0183] In addition, the all-solid-state battery using the support of each embodiment had lower resistance and higher discharge capacity compared to the all-solid-state battery using the support of Comparative Examples 1 to 7.

[0184] Comparative Example 8 could not obtain a support. This is believed to be because the fibrillated fiber used in Comparative Example 8 had a fiber length of 0.04 mm, so it lacked the strength to withstand the manufacturing process.

[0185] That is, from the comparison of each example and Comparative Example 8, it can be seen that the fiber length of the fibrillated fiber used in the support is preferably 0.1 mm or more.

[0186] All-solid-state batteries using the supports of Comparative Examples 1, 5, and 7 have higher resistance and lower discharge capacity compared to all-solid-state batteries using the supports of each embodiment. In addition, the supports of Comparative Examples 1, 5, and 7 have higher perfluoropolyether transmittance in the thickness direction compared to the supports of each embodiment.

[0187] Since the perfluoropolyether permeability in the thickness direction of the supports of Comparative Example 1, Comparative Example 5, and Comparative Example 7 was high at 46.0%, 33.0%, and 37.3%, respectively, the amount of solid electrolyte slurry that the supports could retain was small. As a result, it is believed that the number of carrier ion pass lines in the thickness direction formed inside the solid electrolyte sheet was reduced.

[0188] In the support of Comparative Example 1, non-fibrillated fibers with a large fiber diameter of 16 μm are used compared to each embodiment. As a result, the space in the thickness direction is considered to be larger than that of each embodiment. In the support of Comparative Example 5, fibrillated fibers with a high CSF value of 430 ml and a fiber length of 2.3 mm are used compared to each embodiment. As a result, the space inside the obtained support is considered to be larger than that of each embodiment. In the support of Comparative Example 7, non-fibrillated fibers with a thick fiber diameter of 16 μm and a fiber length of 7 mm are used compared to each embodiment. As a result, when the fibers intertwine, the volume increases and the space inside the support increases.

[0189] That is, from a comparison of each example with Comparative Example 1, Comparative Example 5, and Comparative Example 7, it can be seen that the permeability of the perfluoropolyether in the thickness direction of the support is preferably 30% or less.

[0190] All-solid-state batteries using the supports of Comparative Examples 2, 4, and 6 have higher resistance and lower discharge capacity compared to all-solid-state batteries using the supports of each embodiment. The supports of Comparative Examples 2, 4, and 6 contain 10 mass% of ethylene-vinyl alcohol fibers that undergo shape changes due to moist heat. Because of this, when the supports are formed, a film layer is formed inside the supports rather than in a fiber state, filling the fiber gaps. Accordingly, it is believed that the penetration of the solid electrolyte slurry into the supports is inhibited.

[0191] The support of Comparative Example 4 has a basis weight of 15.5 g / m² 2 Since the number of fibers inside the support is high, it is believed that when a predetermined amount of perfluoropolyether is dropped, the penetration and permeation of the perfluoropolyether in the thickness direction of the support is inhibited. In the support of Comparative Example 6, compared to each example, short, thin fibers with a fiber diameter of 0.7 μm and a fiber length of 0.5 mm are used. Therefore, regarding penetration in the thickness direction of the resulting support, it is believed that the number of fibers inhibiting penetration is large and the penetration and permeation of the perfluoropolyether in the thickness direction of the support is inhibited.

[0192] Compared to the supports of each example, the perfluoropolyether permeability in the thickness direction of the supports of Comparative Examples 2, 4, and 6 was low at 0.4%, 1.5%, and 0.8%, respectively, so the permeation of the solid electrolyte slurry in the thickness direction of the supports was insufficient. As a result, it is believed that the number of carrier ion pass lines in the thickness direction formed inside the solid electrolyte sheet was reduced.

[0193] That is, from a comparison between each example and Comparative Example 2, it can be seen that the amount of synthetic resin binder fibers that cannot maintain a fiber state is preferably less than 10 mass%. In addition, from a comparison between each example and Comparative Example 4, the basis weight of the support is 15.0 g / m² 2 It can be seen that the following is more preferable. From a comparison of each example and Comparative Example 6, it can be seen that the fiber diameter of the non-fibrillated fiber used in the support is preferably 1 μm or more, and the fiber length is preferably 1 mm or more. Additionally, from a comparison of each example and Comparative Example 2, Comparative Example 4, and Comparative Example 6, it can be seen that the permeability of the perfluoropolyether in the thickness direction of the support is preferably 2% or more.

[0194] The all-solid-state battery using the support of Examples 2 and 6 has a higher resistance and lower discharge capacity compared to the all-solid-state battery using the support of Example 4. In addition, the support of Examples 2 and 6 has a higher perfluoropolyether transmittance in the thickness direction compared to the support of Example 4. The perfluoropolyether transmittance in the thickness direction is 28.8% for the support of Example 2 and 29.3% for the support of Example 6, which is higher compared to 23.9% for the support of Example 4.

[0195] In addition, the all-solid-state battery using the support of Examples 1 and 5 has a higher resistance and a lower discharge capacity compared to the all-solid-state battery using the support of Example 3. In addition, the support of Examples 1 and 5 has a lower perfluoropolyether transmittance in the thickness direction compared to the support of Example 3. The perfluoropolyether transmittance in the thickness direction is 2.3% for the support of Example 1 and 2.1% for the support of Example 5, which is lower compared to 4.6% for the support of Example 5.

[0196] That is, from a comparison of Examples 1, 2, 5, and 6 with Examples 3 and 4, the permeability of the perfluoropolyether in the thickness direction of the support is more preferably 4 to 25%.

[0197] Unlike the paper or non-woven fabric supports of each embodiment, the support of Comparative Example 3 is a support in which through holes are formed in a film. Although solid electrolyte can be filled into the through holes of the support of Comparative Example 3, the solid electrolyte can only be filled inside the formed through holes. Furthermore, in the solid electrolyte sheet made of the support of Comparative Example 3, it is believed that an interface exists between the film, which is an insulating material, and the anode or cathode at the interface between the anode or cathode and the solid electrolyte sheet. As a result, the all-solid-state battery using the support of Comparative Example 3 is believed to have a higher resistance and a lower discharge capacity compared to the all-solid-state battery using the support of each embodiment.

[0198] From the comparison of each example and Comparative Example 3, it can be seen that paper and nonwoven fabric are suitable as supports for reducing the resistance of an all-solid-state battery.

[0199] The above-described embodiments are merely examples, and, for instance, the composition of the carrier ion, solid electrolyte, anode, cathode, etc., can be appropriately modified by those skilled in the art.

[0200] As explained above, by using paper and nonwoven fabric with a perfluoropolyether permeability of 2 to 30% in the thickness direction, a support with excellent permeability of solid electrolyte slurry to the support can be obtained. As a result, a required amount of carrier ion pass lines can be formed in the thickness direction of the support. By using this support, an all-solid-state battery with low resistance can be obtained.

[0201] Furthermore, the present invention is not limited to the configuration described in the aforementioned embodiments, and various modifications and changes are possible within the scope of the configuration of the present invention.

Claims

Claim 1 A support for a secondary battery, comprising at least one selected from paper and nonwoven fabric as a support for maintaining a solid electrolyte of a secondary battery, formed from fibrillated fibers and non-fibrillated fibers, and having a permeability of perfluoropolyether in the thickness direction of 2 to 30%. Claim 2 A support for a secondary battery according to claim 1, wherein the content of the fibrillated fiber in the total fiber is 1 to 99 mass%. Claim 3 A support for a secondary battery according to paragraph 2, wherein the content of the fibrillated fiber in the total fiber is 50 to 85 mass%. Claim 4 In claim 1, the paper and the nonwoven fabric are a support for a secondary battery comprising fibers having an average fiber diameter of 1 to 15 μm. Claim 5 In claim 1, the paper and the nonwoven fabric are a support for a secondary battery comprising fibers having a fiber length of 1 to 6 mm. Claim 6 A support for a secondary battery according to claim 1, wherein the CSF value of the fibrillated fiber is 0 to 400 ml. Claim 7 A support for a secondary battery according to claim 1, wherein the fiber length of the fibrillated fiber is 0.1 to 2 mm. Claim 8 A solid electrolyte sheet comprising at least one type selected from paper and nonwoven fabric, wherein a solid electrolyte is retained in a thin film support composed of fibrillated fibers and non-fibrillated fibers, and wherein the permeability to perfluoropolyether in the thickness direction of the support is 2 to 30%. Claim 9 A secondary battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte sheet disposed between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte sheet is made of at least one type selected from paper and nonwoven fabric, and comprises a support composed of fibrillated fibers and non-fibrillated fibers, having a transmittance to perfluoropolyether in the thickness direction of 2 to 30%, and a solid electrolyte retained in the support.